Nuclear Signatures and Stellar Observables: Bridging Terrestrial Experiments and Neutron Star Structure - Koliogiannis Koutmiridis, Polychronis; Yuksel, Esra; Ghosh, Tanmoy; Paar, Nils (HNPS Advances in Nuclear Physics, 2026)
Insights into the properties of dense, neutron-rich matter emerge from the interplay between nuclear experiments and astrophysical observations. Measurements of parity-violating electron scattering on 48Ca (CREX) and 208Pb (PREX-2), together with electric dipole polarizability data, offer stringent probes of isovector dynamics in nuclei. In this study, a set of relativistic energy density functionals is employed to investigate how these nuclear signatures correlate with neutron star observables, such as stellar radii and tidal deformabilities. By confronting the theoretical predictions with data from both terrestrial experiments and multimessenger observations—including the gravitational wave event GW170817—constraints are derived on the symmetry energy and the high-density behavior of the equation of state. The analysis highlights the influence of including the fourth-order term in the isospin-asymmetry expansion of the energy density on neutron star radius and tidal deformability predictions. At the same time, discrepancies between constraints from CREX and PREX-2 underscore the need for improved experimental precision and additional astrophysical input to refine our understanding of dense matter.